Alterations in lung functions based on BMI and Body fat % among obese Indian population at National Capital Region - Kamal, Ritul; Kesavachandran, Chandrasekharan Nair; Bihari, Vipin; Sathian, Brijesh; Srivastava, Anup Kumar (Nepal Journal of Epidemiology, 2015)
Background: In India, non-asthmatic hospital admission case study has been conducted to find out the relationship between obesity and lung functions. The main objective of the present study was to find out the alterations in lung functions due to obesity among Indian population living at National Capital Region (NCR). Materials and Methods: We examined 609 non obese and 211 obese subjects in a cross sectional study from National Capital Region, India with age group ranges between 18-70 years. BMI and body fat % was determined using body fat analyzer. Obese and non-obese subjects were classified based on criteria for BMI and Body fat %. Lung function test viz., FEV1 and PEFR were conducted using portable spirometer (PIKO-1). Results: A significant correlation (p<0.05) was observed between BMI and PEFR among non-obese male and female subjects. Decline in PEFR and FEV1 values for corresponding increase in body fat % was observed among study subjects. A significant (p<0.01) decline in mean FEV1 and PEFR was observed among non-obese and obese subjects, compared to their Indian reference standards for lung functions. A significant negative correlation (p<0.01) was observed between body fat % and lung functions (FEV1, PEFR). Conclusion: It is concluded that obese subjects are at a risk of lung function impairment, based on the criteria followed for BMI and body fat %. The study also demonstrate that body fat% classification as a better index for determination of obese subjects compared to BMI classification, with respect to lung function impairments. DOI: http://dx.doi.org/10.3126/nje.v5i2.12829 Nepal J Epidemiol. 2015;5(2); 470-479.